Activation of Sirtuin 1 Attenuates High Glucose-Induced Neuronal Apoptosis by Deacetylating p53 - Shi, Xiajie; Pi, Linhua; Zhou, Shanlei; Li, Xin; Min, Fangyuan; Wang, Shan; Liu, Zhenqi; Wu, Jing (Frontiers in Endocrinology, 2018)
Diabetes mellitus (DM) is a major risk factor for cognitive impairment. Previous studies have implicated hippocampal neuronal apoptosis in diabetes-related cognitive impairment. However, the underlying mechanism remains unclear. Sirtuin 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD+)-dependent protein deacetylase, is indispensable in normal learning and memory. Whether SIRT1 is involved in diabetes-induced neuronal apoptosis and thus takes part in the development of diabetic cognitive impairment is unknown. To address this issue, we examined the possible role of SIRT1 in hippocampal neuronal apoptosis in streptozotocin-induced diabetic mice and SH-SY5Y cells. We found that downregulation of the activity and expression of SIRT1 was associated with increased hippocampal neuronal apoptosis in mice. Incubation of SH-SY5Y cells with high concentration of glucose induced cell apoptosis which was accompanied by a downregulation of SIRT1 and an increased acetylation of p53. On the contrary, activation of SIRT1 using its agonist resveratrol ameliorated cell apoptosis via deacetylating p53. Our data suggest that high concentration of glucose can induce neuronal apoptosis through downregulation of SIRT1 and increased acetylation of p53, which likely contributed to the development of cognitive impairment in diabetes.